Vision Deterioration and Hydrocephalus: Rare Presentations of Vestibular Schwannoma and Evolution of Management - Keulen, Marte van; Pace, Jonathan; Burant, Christopher J.; Penn, David L.; Wilson, Betsy; Ronald, Andrew; Mowry, Sarah E.; Megerian, Cliff A.; Bambakidis, Nicholas C. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Introduction The incidence of vestibular schwannoma is reported as 12 to 54 new cases per million per year, increasing over time. These patients usually present with unilateral sensorineural hearing loss, tinnitus, or vertigo. Rarely, these patients present with symptoms of hydrocephalus or vision changes.Objective The study aimed to evaluate the surgical management of vestibular schwannoma at a single institution and to identify factors that may contribute to hydrocephalus, papilledema, and the need for pre-resection diversion of cerebrospinal fluid.Patients and Methods A retrospective review examining the data of 203 patients with vestibular schwannoma managed with surgical resection from May 2008 to May 2020. We stratified patients into five different groups to analyze: tumors with a diameter of ≥40 mm, clinical evidence of hydrocephalus, and of papilledema, and patients who underwent pre-resection cerebrospinal fluid (CSF) diversion.Results From May 2008 to May 2020, 203 patients were treated with surgical resection. Patients with tumors ≥40 mm were more likely to present with visual symptoms (p < 0.001). Presentation with hydrocephalus was associated with larger tumor size (p < 0.001) as well as concomitant visual symptoms and papilledema (p < 0.001). Patients with visual symptoms presented at a younger age (p = 0.002) and with larger tumors (p < 0.001).Conclusion This case series highlights the rare presentation of vision changes and hydrocephalus in patients with vestibular schwannoma. We recommend urgent CSF diversion for patients with visual symptoms and hydrocephalus, followed by definitive resection. Further, vision may still deteriorate even after CSF diversion and tumor resection.
Keywords: acoustic neuroma; vestibular schwannoma; hydrocephalus; visual deterioration; papilledema; cerebellopontine angle